Detrimental effect of systemic vascular risk factors on brain hemodynamic function assessed with MRI. Issue 3 (June 2018) - King, Kevin S; Sheng, Min; Liu, Peiying; Maroules, Christopher D; Rubin, Craig D; Peshock, Ron M; McColl, Roderick W; Lu, Hanzhang
Background and purpose: Vascular risk factors have been associated with decreased cerebral blood flow (CBF) but this is etiologically nonspecific and may result from vascular insufficiency or a response to decreased brain metabolic activity. We apply new MRI techniques to measure oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen consumption (CMRO2 ), hypothesizing that decreased CBF related to these vascular risk factors will be associated with increased OEF, confirming a primary vascular insufficiency. Methods: 3T MRI was obtained on 70 community-based participants in this IRB-approved study with informed consent, with previous assessment of systolic blood pressure, hypertension medication, elevated serum triglycerides, low serum HDL, and diabetes mellitus. CBF was measured using phase contrast adjusted for brain volume (ml/100 g/min), OEF (%) was obtained from T2-Relaxation-Under-Spin-Tagging (TRUST), and CMRO2 (μmol/100 g/min) was derived using the Fick principle. Stepwise linear regression identified optimal predictors of CBF with age, sex, and hematocrit included for adjustment. This predictive model was then evaluated against OEF and CMRO2 . Results: Hypertriglyceridemia was associated with low CBF and high OEF. High systolic blood pressure was associated with high CBF and low OEF, which was primarily attributable to those with pressures above 160 mmHg. Neither risk factor was associated with significant differences in cerebral metabolic rate. Conclusion: Low CBF related to hypertriglyceridemia was accompanied by high OEF with no significant difference in CMRO2, confirming subclinical vascular insufficiency. High CBF related to high systolic blood pressure likely reflected limitations of autoregulation at higher blood pressures.